2015
DOI: 10.1098/rsif.2015.0185
|View full text |Cite
|
Sign up to set email alerts
|

Tracking employment shocks using mobile phone data

Abstract: Can data from mobile phones be used to observe economic shocks and their consequences at multiple scales? Here we present novel methods to detect mass layoffs, identify individuals affected by them and predict changes in aggregate unemployment rates using call detail records (CDRs) from mobile phones. Using the closure of a large manufacturing plant as a case study, we first describe a structural break model to correctly detect the date of a mass layoff and estimate its size. We then use a Bayesian classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 65 publications
0
58
0
Order By: Relevance
“…Certainly more work is needed to understand the connection between demographics and predictability. For future research, we suggest considering demographic factors when trying to characterize human mobility, as it has been done, for example, by linking changes in mobility patterns with unemployment status [42].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly more work is needed to understand the connection between demographics and predictability. For future research, we suggest considering demographic factors when trying to characterize human mobility, as it has been done, for example, by linking changes in mobility patterns with unemployment status [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study highlights the potential of mobile phone data to improve forecasts of critical economic indicators such as unemployment rates up to 4 months before the release of official reports, and more accurately than using historical data alone. 15 Our aim will be to compute home/work commuting figures between regions in the country. This objective has been considered one of the simplest involving mobility and has been chosen to start with.…”
Section: Methodological Foundationsmentioning
confidence: 99%
“…Research from David Lazer and his colleagues has shown how mobile phones can lead to better predictions of unemployment rates (7). On the surface, the two don't seem to have anything in common.…”
Section: Mining the Social Networkmentioning
confidence: 99%